The Influence of Electronic Word of Mouth (E-Wom), Brand Image, Product Knowledge on Purchase Intention - I Gusti Ayu Imbayani; Agus Wahyudi Salasa Gama (Universitas Warmadewa, 2018)
In the current era of globalization, the development of science and technology indirectly has a major influence on the economy. During 2017 internet users in Indonesia reached 143.26 million people. The increasing conditions of internet and social media use have now made it easier for people to access and share information about new phenomena, one of which is Go-Jek. Word of mouth, which used to happen personally, now spreads openly through the internet, namely the word electronic word of mouth (e-WOM). The development in the use of internet is increasingly widespread by making companies inevitably have to provide online services, including websites or other online services in order to improve the brand image, product knowledge and purchase intentions. This research is intended to determine to what extent the e-WOM, brand image, product knowledge on purchase intention bring about effects to customer purchase intention. Data were collected using questionnaires distributed to 220 respondents determined through non-probability sampling and accidental sampling. The data analysis technique used is multiple linear regressions. The results of the study show that e-WOM, brand image, product knowledge have a positive and significant influence on purchasing intention.